The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2018
DOI: 10.1177/0891988718813724
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of Cognitive Rehabilitation in Alzheimer Disease: A 1-Year Follow-Up Study

Abstract: Introduction: The benefit of cognitive rehabilitation (CR) for patients with early-stage Alzheimer disease (AD) remains difficult to assess. Method: An observational, prospective study was conducted in a sample of 52 patients with AD included in a clinical, individualized CR program. Cognitive rehabilitation consisted of 1 weekly session during 3 months at home, followed by 1 monthly contact for 9 months. Rehabilitation techniques were used by experienced therapists to adapt activities important for the patien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
1
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 27 publications
(27 citation statements)
references
References 37 publications
0
25
1
1
Order By: Relevance
“…Measuring the benefit of CR for caregivers remains quite difficult. 8 As in our previous study, 21 and contrary to a recent RCT, 7 we could not demonstrate any benefit on caregiver's burden with the classical Zarit burden interview. 16 However, the score on this scale did not increase in the CR group despite an increase in global cognitive impairment.…”
Section: Discussioncontrasting
confidence: 92%
See 1 more Smart Citation
“…Measuring the benefit of CR for caregivers remains quite difficult. 8 As in our previous study, 21 and contrary to a recent RCT, 7 we could not demonstrate any benefit on caregiver's burden with the classical Zarit burden interview. 16 However, the score on this scale did not increase in the CR group despite an increase in global cognitive impairment.…”
Section: Discussioncontrasting
confidence: 92%
“…The procedure is illustrated elsewhere. 21 Briefly, the caregiver had to identify and estimate the difficulties in 98 daily life activities. The total score corresponded to the severity of reported difficulties, with 0 point if no difficulties, 1 point for lack of activity initiation, omission of one or several steps, or wrong execution of one or several steps (maximum 3 points), 4 points corresponding to perseveration errors, and 5 points if the activity could not be carried out; points were summed over all the assessed activities and expressed in percentage of the maximal dependency score.…”
Section: Methodsmentioning
confidence: 99%
“…This decline was lower compared to the average annual rate of change with no treatment reported by other studies: 3.6 points [42], 2.3 points [37], and 2.2 points [13]. Germain et al [43] observed a two-point decrease in the MMSE from baseline to twelve months in AD patients subjected to cognitive rehabilitation.…”
Section: Discussionmentioning
confidence: 69%
“…Ayrıca bu hastaların bakım verenlerinin duygusal tükenmişliğinde kontrollere göre artma olmadığı ve hatta 1 yıl sonraki günlük aktivitelerle ilişkili bakım veren tükenmişliğinde azalma olduğu gösterilmiştir. 25 BR, aynı zamanda yaşam kalitesini iyileştiren ve sağlık kurumuna yatışı geciktiren uygulanabilir bir yaklaşımdır. 26,27 AH sürecinin önemli bir parçası hastaların %90-98'inde görülen, davranışsal ve psikiyatrik belirtilerdir.…”
Section: Erken Evre Alzheimer Hastaliğinda Bi̇li̇şsel Rehabi̇li̇tasyonunclassified